A self-supported ultrathin plasmonic film for ultrafast optical switching. Issue 3 (19th January 2022) - Yang, Jinghui; Fu, Yulan; Zhang, Xinping
Abstract : An ultrafast optical switch is achieved using a self-supported ultrathin plasmonic film. An optical modulation as high as 10% is achieved for a pump fluence of 170 μJ cm −2, implying a flexibly transferable and integrable optical logic device. Abstract : Self-supporting gold nanowire (AuNW) gratings with a thickness of about 200 nm are produced by solution-processing and flexible-transfer techniques. Such an ultrathin structure is applied as an ultrafast optical switch that enables low-threshold optical modulation with a high signal contrast and a high signal-to-noise ratio. Transient energy-band modification in gold under excitation by femtosecond laser pulses is the main responsible mechanism. For a pump fluence of about 170 μJ cm −2, a modulation depth of about 10% is achieved for the optical switching signal. Self-supporting metallic plasmonic photonic thin films with a large area and flexible structures are important for applications in a large variety of circumstances and on different interfaces for optical signal processing, optical logic circuits, and optical communication systems.